Indicadores para Habitação Saudável : uma metodologia aplicada na ZEIS do Bom Jardim em Fortaleza (CE) - Fiuza, Rebeca Freitas (2024)
This research is part of the debate on the influences of the Built Environment on Public Health conditions. Various diseases recur in the same areas, demonstrating the vulnerability of certain territories to health issues. Arboviral diseases, for example, are often linked to poor housing conditions, COVID-19 showed higher fatality rates in low HDI areas of Fortaleza, and some neglected tropical diseases, such as cholera, are connected to the lack of sanitation and bathroom facilities. Relating these facts to the high inadequacy and housing deficit in Fortaleza, as well as the importance of the house as an environment that supports the health of its inhabitants, it is evident that there is a need to explore the intersection of these themes through the lens of housing in vulnerable areas. Therefore, the objective of this research is to develop a methodology for assessing the health and habitability of residences in ZEIS (Special Social Interest Zones), using indicators of healthy housing. The research method adopted was Design Science Research, due to its pragmatic nature of producing knowledge through or for the creation of an artifact. The work is divided into the four phases suggested by the method: problem identification; suggestion; development; and evaluation. The first phase focuses on exploring the research themes and includes the theoretical foundation and literature review, where studies on COVID-19, neglected tropical diseases, arboviruses, and their intersections with indicators and low-income housing were explored. The second stage focused on the suggestion of the artifact, where a healthy housing framework was defined, and the variables to be developed were identified and categorized. The third stage consisted of developing the artifact, where indicators were created using an algorithm that relates the architectural characteristics of housing units with health data, and a database was built from territorial characterization and the collection of primary and secondary data. Finally, the fourth phase involved applying the indicators to housing units surveyed in the field, simulating interventions in one of the houses, and evaluating the performance of the indicators in relation to these modifications. As a result, a Complex Indicator was developed, applied to eight housing units in the ZEIS of Bom Jardim in Fortaleza. This indicator comprises four secondary indicators: Construction Quality; Urban and Environmental Infrastructure; Density; Sanitation; and Natural Lighting. The Complex Indicator allowed for the identification of specific vulnerabilities in each housing unit and the quantification of the effectiveness of potential interventions. This work contributes academically by partially filling a gap in considering health issues within the ZEIS debate, mitigating the absence of evaluative methods that consider all housing characteristics involved in the indicators, and proposing a multidisciplinary data collection method in collaboration with community health agents